Technological Advancements and Implementation Barriers in Clean Coal Utilization: A Systematic Review with Indonesian Case Insights - Muhammad Tri Aditya; Fajar Bagus Gunawan (Publika Bersama Nusantara, 2025)
Coal still plays a major role in Indonesia's energy mix, accounting for approximately 40% of the national primary energy mix in 2024., while low-emission technologies are becoming dominant in the world. In this study, a Systematic Literature Review (SLR) was performed to conduct an evaluation of technological developments and implementation challenges on the clean coal utilization which include gasification, clean combustion systems, activated carbon production and valorization of coal residues (fly ash and bottom ash) from both international view as well as Indonesian perspective. All international and national peer-reviewed articles (published between 2014–2024) were reviewed to analyze trends, gaps, and technical readiness. It is found that coal gasification technology provides the highest energy conversion efficiency of up to nearly 75%, and can cut carbon emissions by 40–60% in comparison to traditional combustion. On the other hand, fly ash and bottom ash utilization of for example 20 million tonnes per year could save up to around Indonesia’s coal power waste generation as well as support circular economy goals. There are still barriers to the adoption of this technology such as high investment costs (1.2–1.5 million/MW), medium moisture in low rank coal (>30%) and small-scale pilot projects at industrial level. Lessons learnt This article reiterates that R&D needs the backing of fiscal incentives, demo plants and regulatory frameworks to hasten the sustainable deployment of CCTs in Indonesia